Characterization of the electron transport chain in mycobacteria - Cardoso, Nicole Collette (My University, 2018)
Mycobacterium tuberculosis (Mtb) has a branched electron transport chain (ETC) with two terminal oxidases, the cytochrome c oxidase (CcO) and the cytochrome bd oxidase (CbdO). The CcO is essential in mycobacteria and is considered the predominantly active terminal oxidase during aerobic respiration. The CbdO on the other hand has been shown to be important under hypoxic conditions in mycobacteria and other organisms. More recently, the mycobacterial CbdO has been implicated in resistance to oxidative stress and in adaptive responses to treatment with ETC-targeting compounds currently being developed for tuberculosis (TB) treatment. The Mtb CbdO has thus been proposed as a promising new drug target. Although mycobacteria are unable to replicate in the absence of oxygen, they are able to survive without it when an alternate electron acceptor is available. This could possibly negate the requirement for either the CcO or the CbdO. An example of this adaptation is the use of nitrate reductase (NR), when nitrate is available as an electron acceptor. The ETC is initiated by the donation of electrons, most commonly by NADH generated during central carbon metabolism (CCM) for the production of energy in the form of ATP. The activity of the ETC is therefore dictated by the available terminal electron acceptors, carbon sources as well as by the available electron donors. Based on these observations we hypothesised that the CbdO contributes to aerobic respiration in mycobacteria. Furthermore, we hypothesised that the availability of different carbon sources or an alternate electron acceptor in the presence of oxygen would affect this activity. We tested our hypotheses using Mtb and Mycobacterium smegmatis strains lacking a functional CbdO or disrupted in genes encoding NR enzymes. The growth and energy-producing capabilities of these strains were evaluated under different conditions including in the presence of alternate carbon sources, in the presence of nitrate and in response to different stresses. We demonstrate that the CbdO is required for optimal ATP production under standard aerobic conditions. Furthermore, the enzyme plays a role in protection against toxic intermediates generated during CCM, particularly when grown on propionate or glycerol. The presence of nitrate was able to restore growth and ATP production in a strain lacking a functional CcO, confirming a role for an alternate electron acceptor under aerobic conditions. In addition, we show that the loss of CbdO leads to a decreased tolerance to oxidative stress, enhanced susceptibility to ETC- and cell wall-targeting drugs and attenuated colonisation of mouse macrophages. Furthermore, we demonstrate that combinatorial loss of both the narB and narGHJI encoded NRs in M. smegmatis does not abrogate NR activity, suggesting that this organism possesses additional NR-encoding genes. Taken together, these data highlight the flexible nature of the mycobacterial electron transport chain and identify the CbdO as an important component of this flexibility, possibly because of its ability to maintain redox homeostasis. Disruption of redox homeostasis as a result of loss of CbdO leads to perturbations in CCM and cell wall biosynthesis and increased oxidative stress, which are collectively detrimental to survival. This supports a case for the development of inhibitors of the mycobacterial CbdO as possible candidates for TB drug development.
A thesis submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy, Johannesburg, 2018